Remnant polarization in thin films from a columnar liquid crystal - Fitié, Carel F. C.; Roelofs, W. S. Christian; Kemerink, Martijn; Sijbesma, Rint P. (Journal of the American Chemical Society, 2010)
Ferroelectric switching is demonstrated in a hydrogen bonded columnar liquid crystalline (LC) material. Polar order induced in the LC phase can be frozen by crystallization of the alkyl chains in the periphery of the columns yielding thin films with remnant polarization and an unprecedented high surface potential as shown by scanning Kelvin probe microscopy.
Gesehen am 17.12.2019